Guidelines for performing Mendelian randomization investigations: update for summer 2023 [version 3; peer review: 2 approved] - Frank Dudbridge; Caroline L. Relton; George Davey Smith; Jean V. Morrison; Zoltán Kutalik; Stephen Burgess; Wei Pan; Dipender Gill; Neil M. Davies; Fernando P. Hartwig; M. Maria Glymour; Cosetta Minelli; et al. (Wellcome Open Research, 2023)
This paper provides guidelines for performing Mendelian randomization investigations. It is aimed at practitioners seeking to undertake analyses and write up their findings, and at journal editors and reviewers seeking to assess Mendelian randomization manuscripts. The guidelines are divided into ten sections: motivation and scope, data sources, choice of genetic variants, variant harmonization, primary analysis, supplementary and sensitivity analyses (one section on robust statistical methods and one on other approaches), extensions and additional analyses, data presentation, and interpretation. These guidelines will be updated based on feedback from the community and advances in the field. Updates will be made periodically as needed, and at least every 24 months.